Management of a pregnant patient with chylomicronemia from a novel mutation in GPIHBP1: a case report - Min-Huan Lin; Xiao-Hui Tian; Xiu-Lan Hao; Hui Fei; Jian-Lan Yin; Dan-Dan Yan; Tian Li (BMC, 2020)
Abstract Background Familial chylomicronemia syndrome (FCS) is a rare autosomal recessive lipid disorder often associated with recurrent episodes of pancreatitis. It is documented in most cases with FCS due to the mutations of key proteins in lipolysis, including LPL, APOC2, APOA5, LMF1 and GPIHBP1. Case presentation We report the successful management of a 35-year-old pregnant woman carrying a novel homozygous frameshift mutation c.48_49insGCGG (p.P17A fs*22) in the GPIHBP1 gene with previous severe episodes of acute pancreatitis triggered by pregnancy, resulting in adverse obstetrical outcomes. With careful monitoring, the patient underwent an uneventful pregnancy and delivered a baby with no anomalies. Conclusions The case report contributes to the understanding of GPIHBP1-deficient familial chylomicronemia syndrome (FCS) and highlights gestational management of FCS patient.